Effective Communication Model of Teachers and Parents in Developing Religious Character of Early Childhood - Hayati, Yayuk Nur; Rofik, Abdur (RAHMATAN LIL ALAMIN: Journal of Peace Education and Islamic Studies, 2023)
Abstract: Teachers and parents have an important role in instilling character in children. A good communication model is considered to have a positive influence on the growth and development of children's character, especially in teaching knowing, feeling and action characters so that they become positive hebituations in children's lives. This study aims to determine the effective communication model of teachers and parents in developing the religious character of early childhood. This research uses a qualitative method of phenomenological type. The research data were collected using observation, interview, and documentation techniques. Then the data was analyzed using the interactive model adapted by Miles, Huberman & Saldana. The results showed that the effective communication model was carried out intensely both directly and indirectly with three patterns, namely Permissive (liberating), Authoritarian (Authoritarian), and Authoritative (democratic). Meanwhile, in an effort to develop a religious character in students, it is carried out with effective communication patterns and flexibility between school members and parents. To strengthen this collaboration, the school facilitates it with the activities of Mental Islamic Spirituality (MKI). Parents are directly involved in developing various religious programs at school. In addition, character development is also carried out using inspirational fairy tales and stories of the Prophets. Where children are asked to listen and retell to their peers. This is done with the intention of providing a bermanka learning experience to children, so that there is an association of understanding and positive attitudes in children that come from fairy tales and stories that have been read.